Automated network profile switcher (ANPROS) - Zakaria, Mohd Zairulhisyam (2007)
Network profile contains the configuration setting of network such as IP addresses on local area network. Usually there will be more than one network profile stored in a notebook of mobile user such as home, office or campus networks. These network profiles apply different setting and configuration. In the campus area, the user will have to apply the campus network profile setting which then enable the users to utilize all network services provided by the network. Dealing with several network profiles make it difficult for the users to manually switch from one profile to another. The users have to reconfigure the IP, subnet mask and default gateway address before they are able to use the network. For average users, these tasks are quite difficult because they have to remember a lots of network information. The Automated Network Profile Switcher (ANProS) solves these problems by providing the user the capability to enable the operating system to automatically switch the network profile without user intervention and restarting the notebook.